Pernicious anemia presenting with dysphagia and melanoderma: a confusing manifestation - Salma Souissi; Myriam Ayari; Imen Abdellali; Rim Bourguiba; Syrine Belakhal; Taieb Jomni; Mohamed Hedi Doggui (Future Science OA, 2024)
Vitamin B12 deficiency is widely recognized as a common cause of anemia. However, symptoms such as dysphagia, melanoderma, and pancytopenia, although less frequent, can also be associated with this deficiency. We report the case of a 47-year-old Caucasian man presented with dysphagia to solids associated to high heart rate, dyspnea and melanoderma. He was diagnosed with severe anemia (hemoglobin 4 g/dl) in association with pancytopenia. Further investigation confirmed that the underlying cause was severe vitamin B12 deficiency secondary to pernicious anemia. Subsequent treatment with vitamin B12 supplements led to a significant improvement in all symptoms. A review of the existing literature corroborated the rarity of severe anemia occurring in conjunction with dysphagia and melanoderma due to B12 deficiency.